Gestational toxoplasmosis treatment changes the child's prognosis: A cohort study in southern Brazil. - Ana Gabriela Gomes Ferrari Strang; Rafaela Gomes Ferrar; Ana Lúcia Falavigna-Guilherme (Public Library of Science (PLoS), 2023)
Background We evaluate the drug treatment for pregnant women with acute toxoplasmosis to reduce the risk of congenital infection, side effects (prenatal and postnatal treatment in children) and the hazard of discontinuing the infant's medication. Methods We conducted a prospective cohort study to assess the risks of congenital toxoplasmosis among children born to acutely infected women with and without treatment. We examined the relationship between "exposed" and "infected children", "number of infant neutrophils", "prenatal" and "postnatal treatment". Factor analysis of mixed data (FAMD) was used to analyze the data. All children started treatment at the hospital. Findings Between 2017 and 2021, 233 pregnant women were evaluated at the University Hospital of Maringá; ninety-four met criteria for acute gestational toxoplasmosis. We followed up 61 children; eleven (18%) had the infection confirmed and 50 (82%) were free of toxoplasmosis (exposed). Children born to untreated mothers have 6.5-times higher risk of being infected; the transmission rate among untreated mothers was 50% versus 8.3% among treated ones. Three decreasing values of immunoglobulin G were a security parameter for stopping the child's medication in the exposed group (50/61). Neutropenia was the leading side effect among children and the infected had a 2.7 times higher risk. There was no correlation between maternal use of pyrimethamine and children's neutropenia. Interpretation The follow-up of women with acute T. gondii infection and their children, through a multidisciplinary team, availability of anti-T. gondii serology and pre- and post-natal treatments reduced the risk of toxoplasmosis transmission.